Grammatical and lexical cohesion devices found in Coldplay's song lyrics in the Ghost Stories album - Putri, Ranadya Ditharifiasari Santoso; Sumiati, Ati (Lililacs Journal, 2022)
This study aims to analyze the used of grammatical devices and lexical device in 9 (nine) Coldplay’s song lyrics in the Ghost Stories album. The songs are titled Always in My Head, Magic, Ink, True Love, Midnight, Another’s Arms, Oceans, A Sky Full of Stars, and O. The source of the data were collected from the lyrics of Coldplay’s song lyrics and taken from Coldplay’s official website. In this study, the writer used theory by Halliday and Hasan (1976) about lexical cohesive devices and grammatical cohesive devices. This study applied qualitative method. The data in this study is in the form of words, phrases, and sentences which contains grammatical and lexical cohesive devices. The result of this study shows that grammatical cohesive devices and lexical cohesive devices were found in Coldplay’s song lyrics in the Ghost Stories album. For the grammatical cohesive devices found are reference, substitution, ellipsis, and conjunction where the dominant types of grammatical cohesive devices used is reference, specifically personal reference.